QUESTIONING CYCLE MODEL IN ENGLISH LEARNING: THE COLLABORATION OF HUMANISM AND CONSTRUCTIVISM APPROACH AT STATE PRIMARY SCHOOLS IN PALEMBANG - Margaretha Dinar Sitinjak; Rita Inderawati; Ida Rosmalina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: This developmental research was aimed to design, try-out, and revise the effectiveness of model in English learning in elementary school. The method in this research was Research and Development (R & D). This research began with the development of learning material, learning process, and instrument evaluation that would be tested limitedly in three elementary schools and 6 teachers and would be tested widely in 15 elementary schools and 30 teachers through questionnaire, observation, interview, and result analysis. The improvement of the final product of questioning cycle model in English learning that collaborated humanism and constructivism approach was based on the feedback in the field trial. The special target that wanted to be achieved in this research was to create an interesting model in English learning for students and learning textbook-centered to make English teaching and learning process easy and fun for primary school pupils. Besides, the model could contribute to scientific publication. Key words: questioning cycle model, English learning, humanism approach, constructivism approach